Development of Islamic Religious Education Materials Based on Religious Moderation in Forming Student Character - Masturin Masturin (Prodi Manajemen Pendidikan Islam Pascasarjana Institut Pesantren KH. Abdul Chalim Mojokerto, 2022)
The model for developing Islamic religious education (PAI) materials based on religious moderation to shape the character of the nation's children at the upper secondary level of education is urgently needed because the phenomena of radicalism and intolerance are spreading in the world of education. In this case the role of the teacher in the learning process is needed to deliver the younger generation in shaping the nation's character. This research focuses on the model of developing Islamic religious education material based on religious moderation, the material is designed according to the values of religious moderation with active learning strategies, and is able to shape character . This study uses a qualitative approach and data collection techniques are used by means of: in-depth interviews, participant observation, documentation, and focus group discussions. Checking the validity of the data through: extending the researcher's presence in the field, triangulation, peer discussions, transferability, dependability, and confirmability. The informants for this study were school principals, students, teachers at senior high schools in Kudus Regency, Central Java, Indonesia. The results of this study indicate that religious moderation-based Islamic education material development models are able to shape the character of students effectively and efficiently. The implication of this study is to become a reference for upper secondary level teachers in the process of learning PAI material. In addition, this research also contribute theoretically to the government in the development of religious moderation-based PAI materials.